Anti-Mullerian hormone (AMH) as predictor of ovarian reserve - Shembekar, Chaitanya Ashok; Upadhye, Jayshree Jayant; Shembekar, Manisha Chaitanya; Welekar, Shravani H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Anti-Müllerian hormone (AMH) is produced by the granulosa cells of preantral and small antral follicles and its levels can be assessed in serum. Since the number of ovarian follicles declines with increasing age, AMH levels might be used as a marker for ovarian ageing. Therefore, we studied the relationship between AMH levels and ovarian response during ovarian stimulation for In vitro fertilization. Methods: A total of 100 patients who have undergone their ICSI treatment cycle using a GnRH antagonist protocol were retrospectively included. Co-relation between AMH and antral follicular count (AFC) was assessed. Results: In present study, 36% patients had normal AMH, 18% patients were in low normal range, 5% patients had low values and 2% patients had very low values. 41% of patients had values in high range suggestive of PCOS. Amongst this, 21% had values between 4 to 8 ng/ml where we got good AFC count and good result in terms of pregnancy. 80% were good responders while 20% were poor responders. When we evaluated the relationship of retrieved oocyte counts with the parameters included, we found that only basal AMH levels and the number of antral follicles were statistically correlated. Conclusions: High AMH levels correlated with low cancellation rates, retrieval of more eggs, higher live birth rates and a high chance for freezing of embryos. Low AMH levels (alone) do not predict low success rates in women under 35 years of age.